A Proposal of a Pension Plan Design Based on Collective Pension Funds - Gómez Hernández, Denise; Banda-Ortiz, Humberto (Mercados y Negocios, 2024)
This work proposes a design of an alternative pension plan based on collectivity with the characteristics of hybrid plans. Based on actuarial methods and financial modeling of some of the variables involved, numerical modeling of collective plans is performed to achieve this objective. Then, various scenarios were carried out to simulate a pension fund based on an institution database. At the end of each period, the replacement rate value for each plan member is calculated with a target of 30% of the last salary. As the plan works collectively, surpluses and deficits are distributed uniformly among the plan members. The results are that it is possible to achieve a replacement rate of 70% in the form of a life annuity due with 30 years of service, a contribution rate of 15% of the salary, and an investment portfolio of 60% of assets invested in equities and 40% in bonds.